2018
DOI: 10.1093/jas/sky450
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Use of pressure mat gait analysis in measuring pain following normal parturition in dairy cows

Abstract: Research investigating the pain of normal parturition is lacking as there are few objective methods for measuring pain. The objective of this research was to describe the gait of cows following eutocia using pressure mat gait analysis; and if meloxicam alters the gait of cows. Twenty Holstein cows within 26 h of unassisted calving were enrolled into the study. Treatment groups included: 1) postpartum cows administered meloxicam (MEL; n = 10); and 2) postpartum cows administered placebo (PLBO; n = 10). Meloxica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…While it may be tempting to prescribe meloxicam in the periparturient period to harvest an increased milk production, in the US, extra-label use of drugs for enhancement of milk production is illegal (13). However, if there were benefits in health parameters as have been proven by our research group (10) and others (12), then extra-label use could be prescribed provided the regulations of the Animal Medicinal Drug Use Clarification Act (AMDUCA) were followed, which included the requirement that no violative drug residues are found in the meat or milk of treated animals (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it may be tempting to prescribe meloxicam in the periparturient period to harvest an increased milk production, in the US, extra-label use of drugs for enhancement of milk production is illegal (13). However, if there were benefits in health parameters as have been proven by our research group (10) and others (12), then extra-label use could be prescribed provided the regulations of the Animal Medicinal Drug Use Clarification Act (AMDUCA) were followed, which included the requirement that no violative drug residues are found in the meat or milk of treated animals (13).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, previous research has shown meloxicam to be efficacious in mitigating pain associated with castration ( 1 ), dehorning ( 2 5 ), mastitis ( 6 ), dystocia ( 7 , 8 ) and diarrhea ( 9 ). Additionally, pain has been evaluated in the post-partum period with a pressure mat and showed that an altered hindlimb weight distribution is likely due to decreased pain associated with meloxicam treatment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, gait analysis was used to support the approval of a transdermal formulation of flunixin, which is the first analgesic compound labeled for cattle to control pain associated with foot rot in the United States (FDA, 2017). The pressure mat gait analysis has also been used to assess pain associated with lameness in cattle and swine, castration in cattle, and parturition in cattle (Pairis-Garcia et al, 2015;Kleinhenz et al, 2018;Kleinhenz et al, 2019). To our knowledge, this is the first study that has used gait analysis to assess pain associated with dehorning in calves.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic gait analysis in cattle has not been well-characterized in the past but is becoming more prevalently used as a diagnostic tool ( Pairis-Garcia et al, 2015 ; Kleinhenz et al, 2018 , 2019a ). A commercially available floor mat–based gait system can be used to assess variables such as gait distance and weight distribution ( Coetzee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%